2014
DOI: 10.1111/ijn.12347
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking in nursing: Scoping review of the literature

Abstract: This article seeks to analyze the current state of scientific knowledge concerning critical thinking in nursing.The methodology used consisted of a scoping review of the main scientific databases using an applied search strategy. A total of 1518 studies published from January, 1999, to June, 2013, were identified, of which 90 met the inclusion criteria.The main conclusion drawn is that critical thinking in nursing is experiencing a growing interest both in the study of its concepts and its dimensions, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 78 publications
0
65
0
3
Order By: Relevance
“…Critical thinking is regarded as an essential clinical skill because it promotes evidence-based professional practice (Chang, Chang, Kuo, Yang, & Chou, 2011;Edwards, Hawker, Carrier, & Rees, 2015;Morténius, Hildingh, & Fridlund, 2016). The concept of critical thinking has been widely explored in the field of university nursing education, but research on critical thinking skills among nurse managers is scarce (Zuriguel-Pérez et al, 2015). According to the International Council of Nursing (CIE) (2017), leadership is essential in nursing management and involves the activities of instructing and mentoring other staff and creating an ideal environment for achieving constant improvements in the quality of care.…”
Section: Backg Rou N D 21 | Critical Thinking As a Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Critical thinking is regarded as an essential clinical skill because it promotes evidence-based professional practice (Chang, Chang, Kuo, Yang, & Chou, 2011;Edwards, Hawker, Carrier, & Rees, 2015;Morténius, Hildingh, & Fridlund, 2016). The concept of critical thinking has been widely explored in the field of university nursing education, but research on critical thinking skills among nurse managers is scarce (Zuriguel-Pérez et al, 2015). According to the International Council of Nursing (CIE) (2017), leadership is essential in nursing management and involves the activities of instructing and mentoring other staff and creating an ideal environment for achieving constant improvements in the quality of care.…”
Section: Backg Rou N D 21 | Critical Thinking As a Competencementioning
confidence: 99%
“…Although it has been shown that critical thinking is influenced by the experience and knowledge acquired during clinical practice, few studies have sought to identify the socio-demographic and occupational factors that can influence RNs' acquisition of critical thinking skills (Zuriguel-Pérez et al, 2015). Some factors of the working environment such as stress, a heavily technical orientation of the care provided, activities that are highly demanding in terms of time and energy, the limited time available, and staff shortages may all hinder the development of critical thinking in clinical practice (Raterink, 2011;Shoulders, Follett, & Eason, 2014).…”
Section: Factors Associated With Critical Thinkingmentioning
confidence: 99%
“…Recommendations have been made for the refinement of existing tools or the development of new ones to overcome these issues (Landis et al, 2007). Critical thinking assessment tools are required to be specific to the nursing discipline and relevant to the specific context for them to be considered reliable and valid (Carter et al, 2015;Feng, Chen, Chen, & Pai, 2010;Newton & Moore, 2013;Perez et al, 2015;Robert & Petersen, 2013;Walsh & Seldomridge, 2006). Some context-specific information for the nursing discipline would include catering for differences in terminology, workforce structures, role expectations and nursing standards particular to a specific country (Jacob, Duffield, & Jacob, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some context-specific information for the nursing discipline would include catering for differences in terminology, workforce structures, role expectations and nursing standards particular to a specific country (Jacob, Duffield, & Jacob, 2017). Currently, tools in use are generic and not specific to the nursing discipline (Perez et al, 2015). One way of ensuring that assessment tools are context-specific is to provide experts with an opportunity to determine the best nursing responses to specific clinical scenarios in a particular country using the Delphi technique.…”
Section: Introductionmentioning
confidence: 99%
“…To develop it, nurses need to be able to think critically, basing their thoughts on a series of skills and behaviours (Cerullo & Cruz, ). The more critical thinking evolves, the greater the ability will be to diagnose each person's specific problems (Bittencourt & Crossetti, ; Cerullo & Cruz, ; Giménez‐Maroto & Serrano‐Gallardo, ; Zuriguel‐Pérez et al., ).…”
Section: Introductionmentioning
confidence: 99%